Memories of Professor François Gros - Takeda, Shin’ichi (Comptes Rendus Biologies)
I joined the laboratory of Professor Francois Gros in 1987 and worked there as a postdoc with Robert Whalen until 1992. I recount the research we carried out and mention that of the other scientists also working on skeletal muscle on the 6th floor of the Molecular Biology Department of the Institut Pasteur at that time. I then present my subsequent research when I returned to Japan. I pay tribute to the influence of Professor Gros and to his support in establishing Japanese/French meetings on muscle biology and muscular dystrophy. I also invoke personal memories of Robert Whalen and Margaret Buckingham and remember the occasions when I returned to Paris to honour François Gros.